Aristotle’s Theory of Regime Change: A Reexamination of Politics 5.1-5.3 - Clifford Angell Bates, Jr (Politeja)
This paper offers a re-examination of Aristotle’s theory of metabole found in the first three chapters of Politics 5. I argue that Aristotle offers a general theory of political change, which highlights the logic and mechanism that will explain not only why regimes will change but also what are the causes and triggers for such change. This paper offers a re-reading of these three chapters showing that what is being addressed here is much more dynamic and useful to contemporary scholars of political science than most presentations of these chapters present.